Imagining liberation: a prophetic literary analysis in Atef Abu Saif’s diary “don’t look left: a diary of genocide” - Andriani, Zulfi Zumala Dwi (JOALL (Journal of Applied Linguistics and Literature), 2025)
This article examines the quest for liberation by Palestinians amidst Israel's assault on the Gaza Strip from October 2023 to December 2023, as documented in Atef Abu Saif's diary, "Don't Look Left: A Diary of Genocide." the diary showed that Palestine experiences kinds of oppression during Israel’s attack. The method used is the descriptive analysis with the theory of Kuntowijoyo's prophetic analysis. There are two kinds of liberation proposed by Kuntowijoyo: external liberation and internal liberation. However, the finding revealed that the Palestinians were only struggling for external liberation. The external liberation that is depicted in Atef's diary is the liberation efforts of Palestinians from some oppressions executed by Israel, such as political oppression, cultural oppression, and economic oppression. The prophetic analysis powerfully indicates the interconnected between religion and social issues. The examination of Atef’s diary also illustrates that the socioeconomic issues confronting Palestine now are intricately linked to the essence of prophecy, asserting that all individuals possess the inherent right to liberation from any form of oppression, irrespective of race, religion, or nationality. Moreover, the Atef's diary illustrates the reality of Palestinian existence under Israeli aggression and offers further insight into war literature grounded on life writing.